BARCODING DNA PADA KOMUNITAS KELELAWAR PEMAKAN BUAH DI INDONESIA - Zein, Moch Syamsul; Fitriana, Yuli Sulistya (Perhimpunan Biologi Indonesia, 2015)
Family Pteropodidae known as fruit bats which has ecological services as seed dispersers, pollinator, and plays important role in the forest regeneration. Identification of bat species frequently encountered problems, i.e., criptic morphology and behaviour. Therefore it is necessary to confirm its identity using DNA barcodes. Cytochrome c oxidase subunit I (COI) mitochondrial DNA is representative of the protein coding mitochondrial DNA and has been used extensively as a means of animal species identification. This study evaluated 141 specimens consist of 42 species and 17 genera which were collected from Java, Nusa Tenggara, Sumatra, Kalimantan, Sulawesi, Maluku, and Papua. Phylogenetic analysis using the neighbor-joining method, in which the genetic distance matrix calculation by Kimura-2 parameter models are implemented on the pairwise distance calculation in the program MEGA version 6:05. The results of the analysis showed variation intraspecific ranging from 0 to 7.9% (0.9 ±0.014%) and there were 4 species with very high intraspecific average sequence divergence, i.e., Penthetor lucasi (3.2%), Thoopterus nigrescens (3.7%), and Chironax melanocephalus (8.7 %). Average interspecific of genetic distance of fruit bats in Indonesia was 20% (1.3-26.1%). These results produce a phylogeny tree construction to form a clearly different cohesive cluster, except in the genus Dobsonia ( D. moluccensis, D. viridis, and D. crenulata), Cynopterus (C. brachyotis C. minutus, and C. luzoniensis), and Macroglossus (M. minimus and M. sobrinus ), because this did not correspond with currently recognized species boundaries based on morphology. Keywords: DNA barcoding, COI, Pteropodidae